Pengaruh Sistem Pengendalian Internal, Whistleblowing System dan Integritas Terhadap Pencegahan Kecurangan dengan Moderasi Perilaku Etis di PT PLN ULP Woha - Rizki Ameliyani; Sumarlin; Namla Elfa Syariati (Academic Bright Collaboration, 2025)
This study aims to determine the effect of the internal control system, whistleblowing system, and integrity on fraud prevention with ethical behavior as a moderating variable at PT PLN ULP Woha. This research uses a quantitative approach with a causal type of research. The population consisted of 49 employees from the energy transactions, engineering, customer service, and administration divisions. Primary data were obtained through direct distribution of questionnaires. Data were analyzed using multiple regression and moderation regression analysis. The results show that the internal control system, whistleblowing system, and integrity have a significant and positive effect on fraud prevention. Ethical behavior moderates the influence of the whistleblowing system and integrity on fraud prevention, but does not moderate the effect of the internal control system. The implication is that PT PLN ULP Woha needs to strengthen internal control policies and procedures, develop a safe and transparent whistleblowing system, and implement training programs to instill integrity and ethical values.